Recent advances in bio-integrated electrochemical sensors for neuroengineering - Shulin Chen; Tzu-Li Liu; Yizhen Jia; Jinghua Li (Fundamental Research)
Detecting and diagnosing neurological diseases in modern healthcare presents substantial challenges that directly impact patient outcomes. The complex nature of these conditions demands precise and quantitative monitoring of disease-associated biomarkers in a continuous, real-time manner. Current chemical sensing strategies exhibit restricted clinical effectiveness due to labor-intensive laboratory analysis prerequisites, dependence on clinician expertise, and prolonged and recurrent interventions. Bio-integrated electronics for chemical sensing is an emerging, multidisciplinary field enabled by rapid advances in electrical engineering, biosensing, materials science, analytical chemistry, and biomedical engineering. This review presents an overview of recent progress in bio-integrated electrochemical sensors, with an emphasis on their relevance to neuroengineering and neuromodulation. It traverses vital neurological biomarkers and explores bio-recognition elements, sensing strategies, transducer designs, and wireless signal transmission methods. The integration of in vivo biochemical sensors is showcased through applications. The review concludes by outlining future trends and advancements in in vivo electrochemical sensing, and highlighting ongoing research and technological innovation, which aims to provide inspiring and practical instructions for future research.